The Role of Agriculture Instructor in Farmer Group Development Coffee Plant (Caffea) (Case Studies: in Jongok Raya Village Bandar Subdistrict Bener Meriah Regency) - Khairunisa Rangkuti; Mailina Harahap; Wien Rezeki (JASc (Journal of Agribusiness Sciences), 2018)
This study aims to examine the role of agricultural extension field in the development of the coffee crop farmer groups and to examine how the development of farmer groups who do agricultural extension to farmers' groups coffee plants. using saturated sample method is by taking the entire population to sampled with a total of 27 respondents. The analytical method used is using the scoring system and descriptive. The results showed that the role of agricultural extension in the development of farmer groups categorized coffee plants already Enough role in carrying out its duties as a teacher, adviser, Analyser and the Organizer. Where the category and the results overall score educator role of farmer groups in the development of the coffee crop farmer group is 1107. The results regarding the development of farmer groups who do agricultural extension to farmers' groups in the village coffee plants belonging Pretty Good Jongok Kingdom where 26 farmers, or 96.3% category Good enough to accept innovation and capability in carrying out activities in the given extension, only 1 or 3.7% of respondents were classified as Less Good was also due to less active in farmer groups.